2021
DOI: 10.3389/fonc.2020.573801
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy and Safety of PARP Inhibitors as Maintenance Therapy in Platinum Sensitive Recurrent Ovarian Cancer: A Network Meta-Analysis

Abstract: This meta-analysis investigated the comparative efficacy and safety of PARP inhibitor monotherapy as maintenance treatment in platinum sensitive recurrent ovarian cancer (ROC). Electronic databases were systematically searched for relevant RCTs. The primary endpoint was PFS. The results were stratified based on three categories: BRCA mutated patients, HRD patients, and overall population. The secondary outcome were discontinuations due to adverse events and grade 3 or 4 adverse events in maintenance phase. Fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…The three PARPis used as monotherapy maintenance therapy for ROC were found to be highly effective in improving PFS as compared with the placebo, and there was no statistical difference between the total population and the BRCAm population, which is consistent with the results of Xu et al. ( 34 ). This provides a basis and the possibility of the expanded use of PARPis to the entire ROC patient population, as does the fact that niraparib and rucaparib can benefit PFS in people with HRD mutations, regardless of positive or negative HRD status.…”
Section: Discussionsupporting
confidence: 88%
“…The three PARPis used as monotherapy maintenance therapy for ROC were found to be highly effective in improving PFS as compared with the placebo, and there was no statistical difference between the total population and the BRCAm population, which is consistent with the results of Xu et al. ( 34 ). This provides a basis and the possibility of the expanded use of PARPis to the entire ROC patient population, as does the fact that niraparib and rucaparib can benefit PFS in people with HRD mutations, regardless of positive or negative HRD status.…”
Section: Discussionsupporting
confidence: 88%
“…The latest result is consistent with in vitro studies demonstrating the higher PARP-trapping potency of talazoparib compared with other PARP inhibitors (6). Results of indirect analysis of the efficiency of olaparib, niraparib, and rucaparib for the treatment of platinum-sensitive recurrent ovarian cancer also demonstrated no statistically significant differences between these agents in terms of PFS (24). Nevertheless, toxicity profiles vary significantly for approved PARP inhibitors, which may play a major role in the selection of specific treatment for PDAC patients.…”
Section: Discussionsupporting
confidence: 82%
“…Recent results have demonstrated that PARP inhibitors could play an emerging role in the maintenance treatment of advanced ovarian cancer with long-term efficacy and improved PFS in patients with newly diagnosed disease experimenting CR or PR to platinum-based chemotherapy (119)(120)(121). According to these results and in the light of the emerging role of PARP inhibitors in the treatment of triple negative breast cancer, there is a solid scientific rationale for the use of these molecules as maintenance therapy even in patients with TNBC.…”
Section: Parp Inhibitors In Triple Negative Breast Cancer Beyond Brca Mutationsmentioning
confidence: 99%